Current research on fungi in chronic wounds - Ge, Yumei; Wang, Qingqing (Frontiers in Molecular Biosciences, 2023)
Chronic wounds are major global health issues. Disordered healing mechanisms always cause these wounds to be difficult to heal. The most common types of chronic wounds are diabetic ulcers, pressure ulcers, arterial/venous ulcers and nonhealing surgical wounds. Bacteria are the most important reason for chronic nonhealing wounds. Misusing some antibiotics to prevent bacterial infections always causes increasing bacterial resistance. Although most studies on chronic wounds focus on bacteria, fungi also have a close relationship with these wounds. Fungi can be recalcitrant to the healing process. Biofilm establishment is the predominant pattern of fungal resistance to antimicrobials or tolerance in chronic non-healing wounds. Fungal species diversity and drug resistance phenotype of chronic wounds will be emphasized. In this review, we outline the latest research on fungi in chronic wounds and discuss challenges and future perspectives related to diagnosing and managing chronic wounds.